Rheumatic fever and rheumatic heart disease among children presenting to two referral hospitals in Harare, Zimbabwe - Gapu, P (S Afr Med J, 2015)
BACKGROUND. Acute rheumatic fever (ARF) and rheumatic heart disease (RHD) remain significant causes of morbidity and mortality in resource-limited settings. In Zimbabwe ARF/RHD characteristics have not been systematically documented. OBJECTIVES. To document cases of ARF/RHD among children presenting at referral hospitals in Harare, Zimbabwe, determine their clinical and echocardiographic characteristics, and identify opportunities for improving care. METHODS. A cross-sectional survey was carried out where consecutive children aged 1 - 12 years presenting with ARF/RHD according to the 2002/3 World Health Organization modified Jones criteria were enrolled. RESULTS. Out of 2 601 admissions and 1 026 outpatient visits over 10 months, 50 children were recruited, including 31 inpatients with ARF/RHD and 19 outpatients with chronic RHD. Among inpatients, 9 had ARF only, 7 recurrent ARF with RHD, and 15 RHD only. The commonest valve lesions were mitral regurgitation (26/31) and aortic regurgitation (11/31). The commonest reason for admission was cardiac failure (22/31). The proportion of ARF/RHD cases among inpatients aged 1 - 12 years was 11.9/1 000. Of the 22 with RHD, 14 (63.6%) presented de novo and 1 had bacterial endocarditis. Among the outpatients, 15 had cardiac failure while echocardiographic findings included mitral regurgitation (18/19) and aortic regurgitation (5/19). At presentation, 18/26 known cases were on oral penicillin prophylaxis and 7 on injectable penicillin. Of those on secondary prophylaxis, 68.0% reported taking it regularly. CONCLUSION. ARF/RHD remains a major problem and cause of hospital admissions in Harare, Zimbabwe. Children often present late with established RHD and cardiac failure. With the majority on oral penicillin, secondary prophylaxis was suboptimal in a resource-limited setting unable to offer valve replacement surgery.